Assessing the Genotoxicity Effect of a Commercial Chlorpyrifos Formulation in Fejervarya limnocharis Tadpoles (Anura: Dicroglossidae) Under Acute and Chronic Exposure - Ramadani, Shima; Marhendra, Agung Pramana Warih; Kurniawan, Nia (Graduate School, Universitas Brawijaya, 2022)
The potential for genotoxicity of pesticides is currently one of the world's concerns. Chlorpyrifos is the organophosphate active ingredient with the largest sales, but the potential for genotoxicity in amphibians is still not widely known. The purpose of this study was to assess the genotoxicity effect of a commercial chlorpyrifos formulation Dursban 200EC in F. limnocharis tadpole erythrocyte (Anura: Dicroglossidae) under acute and chronic exposure using by micronucleus assay. Acute and chronic toxicity tests consisted of negative control, positive control, and 0.4, 0.8, and 1 µg.L-1 of chlorpyrifos with three replications. A toxicity test was carried out on ten tadpoles (Gosner 25) from artificial reproductions in each treatment. The results showed that the formulation of Dursban 200EC in low concentrations (0.4 µg l-1) had the potential to induce DNA damage in erythrocytes of F. limnocharis tadpoles, and there was a positive correlation between chlorpyrifos concentrations and an increase in the frequency of MN. Erythrocytes exposed to chlorpyrifos in both acute and chronic treatment had significantly different MN frequencies between negative and positive controls, 0.4, 0.8, and 1 µg.L-1 (p<0.01). Meanwhile, positive controls were not significantly different from 1 µg.L-1 ( p>0.05). However, the increase in the frequency of MN in chronic treatment was almost twice as high.